EGFR Amplification and Glioblastoma Stem-Like Cells - Katrin Liffers; Katrin Lamszus; Alexander Schulte (Stem Cells International)
Glioblastoma (GBM), the most common malignant brain tumor in adults, contains a subpopulation of cells with a stem-like phenotype (GS-cells). GS-cells can be maintained in vitro using serum-free medium supplemented with epidermal growth factor, basic fibroblast growth factor-2, and heparin. However, this method does not conserve amplification of the Epidermal Growth Factor Receptor (EGFR) gene, which is present in over 50% of all newly diagnosed GBM cases. GS-cells with retained EGFR amplification could overcome the limitations of current in vitro model systems and contribute significantly to preclinical research on EGFR-targeted therapy. This review recapitulates recent methodological approaches to expand stem-like cells from GBM with different EGFR status in order to maintain EGFR-dependent intratumoral heterogeneity in vitro. Further, it will summarize the current knowledge about the impact of EGFR amplification and overexpression on the stem-like phenotype of GBM-derived GS-cells and different approaches to target the EGFR-dependent GS-cell compartment of GBM.